2016
DOI: 10.1111/fog.12180
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability in the feeding and condition of subyearling Chinook salmon off Oregon and Washington in relation to fluctuating ocean conditions

Abstract: Chinook salmon (Oncorhynchus tshawytscha) is one of several economically‐important species of salmon found in the Northeast Pacific Ocean. The first months at sea are believed to be the most critical for salmon survival, with the highest rate of mortality occurring during this period. In the present study, we examined interannual diet composition and body condition trends for late‐summer subyearling Chinook salmon caught off Oregon and Washington from 1998 to 2012. Interannual variability was observed in juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Adult survival of subyearlings examined in this study (fish that entered the ocean in 2011 and 2012 and returned 3 years later to Priest Rapids Dam) was relatively high (>165,000 salmon in each year) compared to 50‐year mean (54,110). Other studies have shown that during years of high survival, subyearlings tend to consume proportionally more invertebrates in September of their first ocean year (Dale et al., ). This may be because certain prey are more abundant during high survival years, or that competition for fish prey is greater during years of high survival, supported by observations that body condition in September is inversely related to survival (Miller et al., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Adult survival of subyearlings examined in this study (fish that entered the ocean in 2011 and 2012 and returned 3 years later to Priest Rapids Dam) was relatively high (>165,000 salmon in each year) compared to 50‐year mean (54,110). Other studies have shown that during years of high survival, subyearlings tend to consume proportionally more invertebrates in September of their first ocean year (Dale et al., ). This may be because certain prey are more abundant during high survival years, or that competition for fish prey is greater during years of high survival, supported by observations that body condition in September is inversely related to survival (Miller et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there appears to be tight coupling between estimated feeding rate and the presence of juvenile anchovy biomass in our surveys. The dominance of anchovy as a prey species for subyearlings in marine waters off Oregon and Washington has been demonstrated over multiple years (1998–2012; Dale, Daly, & Brodeur, ). Anchovy also make up a large proportion of the adult Chinook salmon diet (Thayer, Field, & Sydeman, ), indicating that the availability of this prey type is important during all life stages in coastal waters of the northern California Current.…”
Section: Discussionmentioning
confidence: 99%
“…The ratios of adults returning to Fall Creek did not increase relative to returns to the Willamette River basin, as measured at Willamette Falls, suggesting that ocean conditions may not fully explain the lack of response. Ocean conditions experienced by juveniles are known to be the main drivers of adult Chinook Salmon returns (Dale, Daly, & Brodeur, ). However, we expect that outmigrant Chinook Salmon juveniles produced in other tributaries above Willamette Falls to experience similar or shared ocean conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Warmer-than-average periods in the California Current System reduce food quality and production, shift salmon predator distributions and diets, and reduce early marine survival for Coho and Chinook Salmon (Peterson and Schwing 2003;Wells et al 2016Wells et al , 2017. Higher survival rates occur in years during which salmon enter the ocean when food is plentiful (Duffy and Beauchamp 2011;Wells et al 2012;Dale et al 2016). When food is scarce, early marine survival is low, and only the fish that grow the fastest in the freshwater survive to adulthood (Woodson et al 2013).…”
Section: Climatic Effects On Salmon Habitatmentioning
confidence: 99%